A Comparative Study of Nasal Fiberoptic Intubation with Laryngeal Mask Airway Fiberoptic Intubation in Children with a Difficult Airway - Alireza Mahdavi; Amir Shafa; Seyed Sajjad Razavi; Ahmad Eghbali; Tahere Chavoshi (Archives of Anesthesia and Critical Care, 2023)
Background: Considering that the gold standard for intubation in children with a difficult airway is the use of fiberoptic bronchoscopy, and few studies have evaluated its application in children, the present study aimed at comparing two bronchoscopic techniques of nasal fiberoptic tracheal intubation (FOI-Nasal) and fiberoptic intubation via laryngeal mask airway (FOI-LMA) in children with a difficult airway. Methods: A single-blind randomized clinical trial was performed on 40 six-month-old to six-year-old children that were divided into two groups each consisting of 20 patients.  The participants were all candidates for elective surgery with clinical criteria for the anticipated difficult intubation. FOI-Nasal and FOI-LMA were performed in the first and second groups, respectively. Mean arterial pressure (MAP), heart rate (HR), and blood oxygen saturation levels (SpO2) were assessed and recorded before anesthesia (T1), immediately before bronchoscopy (T2), and immediately after intubation with endotracheal tube (T3). Moreover, ETCO2, the first successful insertion attempt, and the intubation time were recorded, as well. Results: The results of the present study revealed that parameters including MAP, HR, and SpO2 at times T1, T2, and T3 were not significantly different between the two groups after adjusting for potential confounding factors (P> 0.05). However, ETCO2 in FOI-Nasal group with a mean of 38.40 ± 3.57 was significantly higher than that of the FOI-LMA group with a mean of 34.35 ± 3.15 (P = 0.001). In addition, the intubation time in the FOI-LMA group with a mean of 32.40 ± 7.45 was significantly shorter than that of the FOI-Nasal group with a mean of 51.75 ± 9.97 (P <0.001). The success rate in the first attempt in the FOI-Nasal group with the value of 70% was lower than that of the FOI-LMA group with the value of 90%; however, this difference was not statistically significant (P> 0.05). Conclusion: According to the results of the present study, the intubation time in the FOI-LMA group was significantly shorter than that of the FOI-Nasal group. Moreover, the success rate of the first attempt in the FOI-LMA group was higher than that of the FOI-Nasal group. Therefore, it can be stated that FOI-LMA as compared to FOI-Nasal can be regarded as an easier technique, with a shorter intubation time, a higher success rate, and a greater stability of children’s hemodynamic parameters.